Student and Educator Perspectives of Adapting to Remote Health Professions Education: A Mixed-Methods Study - Sarkar, Mahbub; Liu, Karen; Kumar, Arunaz; Ilic, Dragan; Morphet, Julia; Maloney, Stephen; Davis, Elizabeth; Palermo, Claire (Frontiers in Medicine, 2022)
During the COVID-19 pandemic, universities across the world transitioned rapidly to remote education. Engaging with a curriculum that has been transitioned from in-person to remote education mode is likely to impact how students and educators adapt to the changes and uncertainties caused by the pandemic. There is limited knowledge about individual differences in students’ and educators’ adaptability to remote education in response to the pandemic. This paper explored healthcare students’ and educators’ adaptability experiences to remote education. Drawing on pragmatism, a convergent mixed-methods design was adopted. An online survey was undertaken, followed by interviews with students and educators of five large health courses at an Australian research-intensive university. Data included 476 surveys and seven focus group interviews with 26 students, and 95 surveys and 17 individual interviews with educators. Results were interpreted through an integration of quantitative and qualitative elements from student and educator experiences. Findings indicated that students were less adaptable than educators. Whilst remote learning was less appealing than in-person learning, some students adapted well to the new learning environment. Limited social learning, transmissive pedagogy, and lack of clinical and technical skills were identified as factors that impacted upon the experience of students and educators. Navigating the challenges associated with remote education provided students and educators with a unique opportunity to improve adaptability—an attribute critical for future uncertainties in healthcare practice.